Optical Frequency Comb Generation in Highly Nonlinear Fiber With Dual-Mode Square Microlasers - Hai-Zhong Weng; Yong-Zhen Huang; Xiu-Wen Ma; Yue-De Yang; Jin-Long Xiao; Jun-Yuan Han; Ming-Long Liao (IEEE Photonics Journal, 2018)
Optical frequency comb (OFC) generation based on four-wave mixing in highly nonlinear fiber (HNLF) is investigated using dual-transverse-mode square microlaser as a seed source. Dual-mode lasing microlasers with wavelength intervals from 1.11 to 0.36 nm are realized and applied for OFC generation at different square side lengths. For an 18- μm-side-length microlaser, a frequency comb with 50 nm bandwidth and 102 GHz line spacing is achieved using two stages of erbium-doped fiber amplifier and HNLF. A phase-locked comb with a pulse width of 1 ps is also verified using frequency resolved optical gating analyses. In addition, the comb linewidths are nearly linearly increased with the comb order, which is in agreement with the linewidth behavior determined by 1/ f noise. The results indicate that 1/f noise deteriorates the laser linewidth greatly.